Global public health security and justice for vaccines and therapeutics in the COVID-19 pandemic. (September 2021) - Hotez, Peter J.; Batista, Carolina; Amor, Yanis Ben; Ergonul, Onder; Figueroa, J Peter; Gilbert, Sarah; Gursel, Mayda; Hassanain, Mazen; Kang, Gagandeep; Kaslow, David C.; Kim, Jerome H.; Lall, Bhavna; et al.
Abstract: A Lancet Commission for COVID-19 task force is shaping recommendations to achieve vaccine and therapeutics access, justice, and equity. This includes ensuring safety and effectiveness harmonized through robust systems of global pharmacovigilance and surveillance. G lobal production requires expanding support for development, manufacture, testing, and distribution of vaccines and therapeutics to low- and middle-income countries (LMICs). Global intellectual property rules must not stand in the way of research, production, technology transfer, or equitable access to essential health tools, and in context of pandemics to achieve increased manufacturing without discouraging innovation. Global governance around product quality requires channelling widely distributed vaccines through WHO prequalification (PQ)/emergency use listing (EUL) mechanisms and greater use of national regulatory authorities. A World Health Assembly (WHA) resolution would facilitate improvements and consistency in quality control and assurances. Global health systems require implementing steps to strengthen national systems for controlling COVID-19 and for influenza vaccinations for adults including pregnant and lactating women. A collaborative research network should strive to establish open access databases for bioinformatic analyses, together with programs directed at human capacity utilization and strengthening. Combating anti-science recognizes the urgency for countermeasures to address a global-wide disinformation movement dominating the internet and infiltrating parliaments and local governments.